2007
DOI: 10.1128/aac.00120-07
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Novel Rifamycin Derivative, ABI-0043, against Staphylococcus aureus in an Experimental Model of Foreign-Body Infection

Abstract: We compared the efficacy of a novel rifamycin derivative, ABI-0043, with that of rifampin, alone and in combination with levofloxacin, against methicillin-susceptible Staphylococcus aureus ATCC 29213 in a guinea pig tissuecage infection model. The MIC, logarithmic-growth-phase minimal bactericidal concentration, and stationarygrowth-phase minimal bactericidal concentration of ABI-0043 were 0.001, 0.008, and 0.25 g/ml, respectively; the corresponding concentrations of rifampin were 0.016, 0.8, and 3.6 g/ml, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 36 publications
(51 reference statements)
3
34
0
Order By: Relevance
“…Thus, a recent study by Trampuz et al described results similar to those previously reported with the combination of rifampin and classical fluoroquinolones when rifampin and levofloxacin were used at very low doses (C max , 0.97 g/ml) in a guinea pig model of staphylococcal foreign-body infection (42).…”
Section: Vol 52 2008 Effect Of Rifampin On High-dose Levofloxacin 3683supporting
confidence: 73%
“…Thus, a recent study by Trampuz et al described results similar to those previously reported with the combination of rifampin and classical fluoroquinolones when rifampin and levofloxacin were used at very low doses (C max , 0.97 g/ml) in a guinea pig model of staphylococcal foreign-body infection (42).…”
Section: Vol 52 2008 Effect Of Rifampin On High-dose Levofloxacin 3683supporting
confidence: 73%
“…This effect could result from the fact that cell wall synthesis is reduced in SCVs (40). In contrast, daptomycin, aminoglycosides, fluoroquinolones, oritavancin, and, to a lesser extent, rifampin have been shown to remain bactericidal against extracellular slow-growing bacteria (11,33,37,54).…”
Section: Discussionmentioning
confidence: 94%
“…The rifampin dose of 12.5 mg/kg was chosen as described previously (31,34). The peak levels in tissue fluid were equal to or less than the maximal concentrations reached in humans (1), and the rifampin concentration in cage fluid was greater than the MIC during 12 h after administration.…”
Section: Discussionmentioning
confidence: 99%
“…The test The mean values of C max and AUC 0-24 in cage fluid after administration of a single intraperitoneal dose were used. Pharmacokinetic data for rifampin and levofloxacin were described previously (22,31). organism was inhibited by linezolid at 2.5 g/ml.…”
Section: Discussionmentioning
confidence: 99%